2009
DOI: 10.1126/science.1169628
|View full text |Cite
|
Sign up to set email alerts
|

RNA Pol II Accumulates at Promoters of Growth Genes During Developmental Arrest

Abstract: When Caenorhabditis elegans larvae hatch from the egg case in the absence of food, their development is arrested (L1 arrest), and they show increased stress resistance until food becomes available. To study nutritional control of larval development, we analyzed growth and gene expression profiles during L1 arrest and recovery. Larvae that were fed responded relatively slowly to starvation compared with the rapid response of arrested larvae to feeding. Chromatin immunoprecipitation of RNA polymerase II (Pol II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
206
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(227 citation statements)
references
References 20 publications
20
206
1
Order By: Relevance
“…The distribution of elongating Pol II, relative to the TSS, was essentially identical in all of the strains (Fig. 2C), similar to previous reports (23,25).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The distribution of elongating Pol II, relative to the TSS, was essentially identical in all of the strains (Fig. 2C), similar to previous reports (23,25).…”
Section: Resultssupporting
confidence: 79%
“…However, 5095 was recently shown to also recognize unphosphorylated Pol II in C. elegans (23). The CTD heptad repeat-specific antibody (8WG16) is phosphorylation independent (24) and has been used previously for C. elegans ChIPs (23,25). ChIP signals throughout the marked genes were much stronger with 5095 compared with 8WG16 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…How this information is transduced to affect gene expression in response to a given stimulus is currently speculative at best. During starvation in C. elegans L1 larvae, a specific geneexpression program is initiated (46) and during this period RNA polymerase II is observed in different configurations: in the "docked" state RNA polymerase II is on proximal promoters waiting for cues to initiate, whereas in the "paused" configuration the complex remains in a postinitiated state, presumably on hold until a physiological or developmental contingency is satisfied (47,48). This developmental pausing is not exceptional and in many organisms RNA polymerase II is maintained in a postinitiated state where subsequent elongation is regulated by factors that associate with the phosphorylated carboxyl-terminal domain of the RNA polymerase II large subunit (49).…”
Section: N="normal"mentioning
confidence: 99%
“…We found that a motif matching the known specificity of DAF-16 (GTTGTTTAC) is significantly enriched in daf-2/daf-16 mutant experiments (McElwee et al, 2004). DAF-16 has also been shown to be involved in starvation response in C. elegans (Henderson and Johnson, 2001), and samples from starvation experiments (Baugh et al, 2009) are significantly enriched for the same motif.…”
Section: Evaluation Of Magma C Elegans Motifsmentioning
confidence: 61%